Attention-Setting and Human Mental Function - Thomas Sanocki; Jong Han Lee (Journal of Imaging, 2022)
This article provides an introduction to experimental research on top-down human attention in complex scenes, written for cognitive scientists in general. We emphasize the major effects of goals and intention on mental function, measured with behavioral experiments. We describe top-down attention as an open category of mental actions that initiates particular task sets, which are assembled from a wide range of mental processes. We call this attention-setting. Experiments on visual search, task switching, and temporal attention are described and extended to the important human time scale of seconds.